Spatio-Temporal Variation of Soil Phosphorus and Its Implications for Future Pomelo Orcharding System Management: A Model Prediction From Southeast China From 1985–2100 - Yan, Xiaojun; Li, Guohua; Zhang, Weiqiang; Muneer, Muhammad Atif; Yu, Wenjia; Ma, Changcheng; Wu, Liangquan (Frontiers in Environmental Science, 2022)
Phosphorus (P) is a non-renewable source, requires in large amount for maintaining better crop growth and development. The excessive P fertilizer contributes to the accumulation of P in the soil and results in increased soil total P and Olsen P. However, the spatio-temporal variation of soil P remains unclear in pomelo orchard systems. Therefore, this study aimed to assess the temporal and spatial variation of soil P in pomelo orchards and future to predict P pool from 1985 to 2100, based on the dynamic P pool simulator (DPPS) model. We found that an average of 282.23 kg P ha−1 yr−1 accumulated in pomelo orchard soil, resulting in increased concentration of Olsen P (i.e., 5–212 mg kg−1) and total P (i.e., 80–1883 mg kg−1) in the topsoil. It showed that Olsen P and total P pools increased in topsoil about 42 and 25 folds, respectively from 1985 to 2015. Soil P accumulation occurred not only in topsoil but also found in deeper soil horizon of pomelo orchard. Compared with the natural forest, the concentration of Olsen P and fractions (Al-P and Fe-P) in 20-year-old pomelo orchard increased significantly in soil depth of 0–120 cm, while Sol-P increased significantly in 0–60 cm soil depth. Scenario analyses from 1985 to 2100 indicated that the P application rate at 31 kg P ha−1 could maintain pomelo yield at its optimum level. These findings could provide the synthesized novel insight for understanding the soil P status and its sustainable management in the pomelo orchard systems.